Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behaviour (OCB) pada PT Graha Sarana Duta (Telkom Property) - Noviayanti Fitri Haryani; Ferryal Abadi (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of organizational culture and job satisfaction on organizational citizenship behavior (OCB) at PT Graha Sarana Duta (Telkom Property). This type of research used in this study is to use quantitative methods with probability sampling techniques. In this study, the authors used quantitative data from the results of distributing questionnaires via google form to respondents. The sample of this research is 35 respondents who are employees of PT Graha Sarana Duta (Telkom Property). Data processing was carried out in this study using SPSS version 22 software.The results showed that the organizational culture variable had a significant effect on job satisfaction, the job satisfaction variable had a significant effect on Organizational Citizenship Behavior (OCB) and the Organizational Culture variable had a significant effect on Organizational Citizenship Behavior (OCB).